Immunological Impact of Intestinal T Cells on Metabolic Diseases - Zhou, Haiyan; Wang, Liwen; Liu, Feng (Frontiers in Immunology, 2021)
Emerging evidence accumulated over the past several years has uncovered intestinal CD4+ T cells as an essential mediator in modulating intestinal immunity in health and diseases. It has also been increasingly recognized that dietary and microbiota-derived factors play key roles in shaping the intestinal CD4+ T-cell compartment. This review aims to discuss the current understanding on how the intestinal T cell immune responses are disturbed by obesity and metabolic stress. In addition, we discuss how these changes influence systemic metabolic homeostasis and the T-cell-mediated crosstalk between gut and liver or brain in the progression of obesity and its related diseases. Lastly, we highlight the potential roles of some drugs that target intestinal T cells as a therapeutic treatment for metabolic diseases. A better understanding of the interaction among metabolites, bacterial signals, and T cell immune responses in the gut and their roles in systemic inflammation in metabolic tissues should shed new light on the development of effective treatment of obesity and related disorders.